Urban Poverty Enclaves and Ecological Risks: Uncovering the Boomerang Effect in South Tangerang - Anugrah, Gilang Tresna Putra; Ratnasari, WG Pramita; Hermansah, Tantan; Rahmawati, Isna; Ratnasari, Nofia (Ijtimaiyya: Jurnal Pengembangan Masyarakat Islam, 2026)
The rapid development of South Tangerang City creates a spatial dualism, with elite areas coexisting alongside vulnerable poverty pockets. Macro-level approaches often fail to capture how poverty interacts with environmental degradation. Through a quantitative survey method of 417 respondents, this study aims to map micro-poverty profiles and analyze their risks to the city's ecological future. The results reveal that urban poverty is structural and spatially stigmatized. Low-income residents are not only trapped in subsistence livelihood strategies but also experience severe urban infrastructure injustice, characterized by a massive reliance on shallow groundwater (49.64%) and unsafe on-site sanitation (88.97%). The novelty of this research lies in providing empirical evidence of the nexus between micro-level poverty and macro-level threats of environmental degradation. Theoretically, this study contributes to expanding the urban political ecology framework by demonstrating how neglecting basic infrastructure in marginalized areas triggers a boomerang effect. The accumulation of water contamination risks confirms that ecological threats stemming from poverty transcend spatial segregation boundaries, potentially becoming an ecological time bomb that jeopardizes the city's future resilience.